An integrated blended learning approach for physical education teacher education programmes: teacher educators' and pre-service teachers' experiences. (2nd November 2021) - Calderón, Antonio; Scanlon, Dylan; MacPhail, Ann; Moody, Brigitte
ABSTRACT: Background : A plethora of new terms and digital pedagogies have been making recent headlines in higher education with the promise, or threat, that digital technology will revolutionise the way in which universities operate. Blended learning is part of this digital revolution and institutions of higher education worldwide are increasingly adopting it as a new mode of delivery. The exposure of blended learning as central to mainstream higher education has been heightened exponentially during the COVID-19 pandemic. Purpose : Challenged by the argument around the concept of 'blended' being ill defined, and also given the lack of practical 'blended' experiences in physical education teacher education (PETE), this paper aims to explore physical education teacher educators' and pre-service teachers' (PSTs') enactment and experiences of an integrated approach to blended learning. Method : Three physical education teacher educators and two classes of physical education PSTs participated. The integrated blended approach was designed through a block structure which allowed intended outcomes, teaching and learning activities and assessment tasks to be aligned and interconnected. Data collection occurred over two academic years for the same three physical education teacher educators and two different cohorts of PSTs. Focus groups interviews were conducted with the three teacher educators and a voluntary sample of PSTs. PSTs' learning blogs were also analysed. Results : Findings were presented in three categories: Development of strong building blocks; Blended learning 'releases the teaching and learning from the grips of the lecturer'; and Assessment in a blended (and non-blended) environment. We attempted to go beyond the binary humanist assumption about blended learning by designing an integrated approach with a clear but flexible structure. That is, with an organic alignment and purposeful integration of all its instructional components. Conclusions : When introducing blended learning in a (physical education) teacher education programme, we suggest designing an aligned and integrated approach structured in blocks, where all instructional components are interconnected and informing each other, enhancing prior knowledge. Given the growing role of digital technology for teaching and learning in educational policies and new PETE curricula, we advocate for the publication of more research-based experiences on blended learning in PETE programmes that might be replicated in other PETE programmes. This would encourage colleagues to explore the implications of digital technology and learn from other PETE contexts and also the sustainability of digital technology as an established mode of delivery.